Technical-economic prospect for photovoltaic on fixed lift net in Indonesia - I Made Aditya Nugraha; I Gusti Made Ngurah Desnanjaya; Jhon Septin Mourisdo Siregar; Lebrina Ivantry Boikh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The limited fossil energy and uncertain prices have an indirect effect on fishing activities using a fixed lift net. Therefore, energy diversification is carried out by utilizing solar energy with photovoltaics on the fixed lift net. This energy is very abundant and available throughout the year, except during the rainy season. This study uses observation, interviews, and questionnaires given to fishermen and tries to compare the utilization of photovoltaic (PV) systems with generators using different types of lamps, such as LED, CFL, incandescent lamps, and halogen lamps. The use of PV systems in fixed lift nets from a technical and economic perspective allows it to be utilized in the long term. Based on the technical aspects, the PV system can produce 471.59 Wh per day. This technical result will be more profitable if the lamp used is a light emitting diode (LED) lamp. Meanwhile, from economic aspect, the use of electrical energy from a PV system is more profitable because it provides a lower operational value than a generator, and provides good net present value (NPV) and internal rate of return (IRR) values. This utilization is also supported by the good response from fishermen towards the energy produced and the ease of operation and maintenance of the PV system.